BS EN 62282-8-301. Fuel cell technologies. Part 8-301. Energy storage systems using fuel cell modules in reverse mode. Power to methane energy systems based on solid oxide cells including reversible operation. Performance test methods (11th October 2021) - British Standards Institution,
No abstract available